Balancing Tradition and Science: Acupuncture in Pain Control - Grzelak, Alicja (Journal of Education, Health and Sport, 2024)
Introduction: Pain management is a critical component of healthcare, addressing acute and chronic conditions that significantly impact quality of life. Traditional pharmacological approaches, while effective, often present side effects and dependency risks. Acupuncture, rooted in traditional Chinese medicine, has emerged as a complementary and alternative therapy, leveraging the body’s natural mechanisms to alleviate pain through the strategic insertion of fine needles at acupoints. Purpose of Work: This research investigates the role of acupuncture in pain management, examining its efficacy across various pain conditions, understanding its physiological mechanisms, and evaluating its integration into modern medical practice. It seeks to assess the scientific evidence supporting acupuncture and its potential as a non-pharmacological pain management strategy. State of Knowledge: Studies have demonstrated acupuncture's effectiveness in reducing pain intensity for conditions such as migraines, osteoarthritis, fibromyalgia, and postoperative pain. Mechanistic research highlights its role in modulating neural pathways, enhancing endogenous opioid release, and reducing inflammation. Guidelines from health organizations now recognize acupuncture as a viable option in multidisciplinary pain management. Material and methods: The study methodology entailed defining the objectives, conducting a systematic literature search, and implementing a structured process for screening relevant studies. The research encompassed a comprehensive search across scientific databases, such as PubMed and Google Scholar. Summary: Acupuncture presents a promising, evidence-supported intervention for pain management. By combining traditional techniques with modern scientific insights, acupuncture addresses the growing need for holistic, safe, and effective approaches to alleviating pain and enhancing patient well-being.